Comparison of K2 and K3 EDTA Anticoagulant on Complete Blood Count and Erythrocyte Sedimentation Rate - Harida Zahraini; Yulia Nadar Indrasari; Hartono Kahar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
The use of anticoagulants is one of the important pre-analytic factors in hematological tests. Both dipotassium (K2) andtripotassium (K3) Ethylene Diamine Tetraacetic Acid (EDTA) are widely used anticoagulants. International CouncilStandardization of Hematology (ICSH) and several researchers recommend the use of K2 EDTA due to its less hyperosmolareffect on blood cells compared to K3 EDTA. This study aimed to compare the results of Complete Blood Count (CBC) andErythrocyte Sedimentation Rate (ESR) using anticoagulant K2 EDTA and K3 EDTA. This study was an analytic observationalstudy with a cross-sectional design conducted from April to December 2018. The subject of the study were 103 healthyadults selected by consecutive sampling. Blood samples were collected in both anticoagulant tubes with a volume of 3 mLeach. Samples were tested twice, in the first 0 hours and the next 6 hours using Sysmex XN 1000 and Alifax Roller 20 LC.Kolmogorov-Smirnov test, paired T-test and Wilcoxon rank test were used for statistical analysis. The agreement testbetween both anticoagulants was carried out using the Bland Altman plot for parameters with a significant difference. Therewas a significant difference between both anticoagulants for the parameters of hemoglobin, hematocrit MCV, MCHC, RDW,PDW, MPV, PLC-R, and erythrocyte sedimentation rate in both the first and second tests. The agreement test using the BlandAltman plot showed that the difference in these parameters was within the Limit of Agreement (LOA) range of 95%. Thisstudy showed that there were differences in some parameters of complete blood count and erythrocyte sedimentation ratebetween the two anticoagulants (K2 K3 EDTA), but these differences were within the LOA range.